Quality Management Strategies in Facing the Resilience Crisis of Elementary Madrasahs in the 5.0 Era - Nurul Hidayah; Imam Syafe'i; Ahmad Fauzan; Koderi Koderi; Agus Pahrudin (Nazhruna: Jurnal Pendidikan Islam, 2025)
This study was motivated by the challenges faced by madrasah ibtidaiyah in maintaining the quality of education amid limited resources and the demands of the Society 5.0 era, which requires adaptation to technology and social change. The gap between the ideal of educational quality and the actual conditions in the field underscores the need for practical, adaptive quality management strategies. Therefore, this study aims to analyse quality management strategies to address the resilience crisis in madrasah ibtidaiyahs, enabling them to maintain and improve their quality amid limitations. This study uses a qualitative case study approach conducted at Madrasah Ibtidaiyah Negeri 5 Bandar Lampung and Madrasah Ibtidaiyah Terpadu Muhammadiyah Bandar Lampung. Data were collected through interviews, observations, and documentation, then analysed using the Miles and Huberman model through the stages of reduction, data presentation, and conclusion drawing. The results of the study show that quality management strategies in both madrasahs are implemented through the visionary leadership of the madrasah principal, a culture of participatory deliberation, teacher competency development, creativity enhancement, and active student involvement in the learning process. Factors supporting this strategy include the spirit of teacher innovation, student participation, and collective awareness of the importance of quality education. The implications of this study emphasise the importance of strengthening teachers’ digital literacy, fostering a culture of collaboration, and securing external support from the government and community to enhance madrasah resilience in the era of Society 5.0.